Systematic Literatur Review (SLR) : Analisis Faktor Penyebab Kesulitan Belajar Siswa Sekolah Dasar Pada Pembelajaran Matematika - Nur Hanifah; Muhammad Sya’ban Zakiya; Oktaviana Dwi Rahmadhani; Inez Avista Rini; Fina Fakhriyah; Erik Aditya Ismaya (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this research is to analyze the causes of learning difficulties for elementary school students in learning mathematics, and to find out what materials students think are difficult to understand in learning mathematics. This study uses the Systematic Literature Review (SLR) method. The aim of the research is the Systematic Literature Review (SLR) method to evaluate, review and recognize relevant research so as to be able to answer questions on the specified research. The results of the study show that the factors causing learning difficulties for elementary school students in learning mathematics are, that internal factors include (1) Interest, students who are less interested in participating in mathematics learning, plus students in the class who are less focused and serious in participating in the teaching and learning process as seen by students always leads to the outside of the class when the teacher explains the material, (2) Factors of students' learning habits, less precise learning of students who only study when there is a test (3) Health factors of students, can affect the level of concentration of students in learning mathematics, if the student body is lacking healthy then it can affect student learning outcomes.